Description of Nutritional Status Based on MUAC with Adolescent Level of Knowledge About CED and Stunting at SMAN 19 Surabaya - Vira Varamida; Inne Soesanti; Ani Intiyati (Politeknik Kesehatan Kemenkes Surabaya, 2025)
Chronic Energy Deficiency (CED) is a nutritional problem among adolescents that increases the risk of giving birth to babies with low birth weight and stunting. This study aims to describe the knowledge level of adolescent girls about CED and stunting, as well as their nutritional status based on Mid-Upper Arm Circumference (MUAC) measurements at SMAN 19 Surabaya. This descriptive observational study used a simple random sampling technique with informed consent from respondents. Data were collected through interviews using questionnaires to assess knowledge, and MUAC measurements to evaluate nutritional status. The data were then analyzed using cross-tabulation. The results showed that most respondents had sufficient knowledge about CED (47.2%) but poor knowledge about stunting (52.8%), with the majority categorized as non-CED based on MUAC. Cross-tabulation indicated that knowledge is not always directly associated with nutritional status, particularly regarding stunting. These findings highlight the need for integrated school-based nutrition education programs to mitigate the intergenerational impact of malnutrition and stunting.